VERBALIZATION OF MYTHOLOGEMES IN THE UZBEK LITERARY TEXT (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
The article discusses the concept of mythologemes in Uzbek literary texts and more specifically dwells on the articulation of these basic structural units of myth. The study, based on research into their function in Uzbek folklore and classical and contemporary narratives, looks at how mythologemes can serve to underpin the development of cultural identity, world vision, and collective consciousness in Uzbekistan. Within the frameworks of structuralist theory and cultural linguistics, we will be able to analyze in this paper the verbal forms and narrative functions of mythologemes, holding cultural values and historical traditions in Uzbek literature